Moral Self-Realization in Kant and Spinoza. - Kozyra, Wojciech (Problems / Problemos, 2022)
Spinoza and Kant are considered to be polar opposites with respect to ethics. The radical difference between them is supposed to consist in Spinoza's ethical egoism, or interest-based Strebensethik, and Kant's duty-cantered, deontological Sollensethik. I challenge this opposition and argue that both in Kant and Spinoza we deal with a notion of the self's realization that is "interest"-based and therefore does not involve self-sacrifice. I show, on the one hand, that the streben in Spinoza's Strebensethik consists in realising one's essentially human interest, which resides in ethical-rational action, and, on the other hand, that sollen in Kant's Sollensethik is in fact a streben of the Kantian "proper self" (eigentliches Selbst) after the realization of its ethical-rational interest.